2005
DOI: 10.2165/00044011-200525070-00002
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol SR Formulations

Abstract: Although tramadol SR capsules and tramadol SR tablets led to an equivalent systemic exposure to the drug, capsules provided a smoother and more extended plasma profile. In addition, in the case of capsules, bioavailability was subjected to lower variability in terms of both rate and extent of absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Extended-release (ER) or controlled-release (CR) formulations may improve opioid tolerability in OA patients by preventing the high plasma peaks that are associated with the AEs observed with the immediate-release (IR) formulations [18]. A meta-analysis of four RCTs of patients with musculoskeletal pain found that ER tapentadol (100–250 mg/day) is associated with a reduction in pain intensity in comparison with placebo and oxycodone.…”
Section: Introductionmentioning
confidence: 99%
“…Extended-release (ER) or controlled-release (CR) formulations may improve opioid tolerability in OA patients by preventing the high plasma peaks that are associated with the AEs observed with the immediate-release (IR) formulations [18]. A meta-analysis of four RCTs of patients with musculoskeletal pain found that ER tapentadol (100–250 mg/day) is associated with a reduction in pain intensity in comparison with placebo and oxycodone.…”
Section: Introductionmentioning
confidence: 99%
“…Лекарственные формы трамадола с замедленным высвобождением (ЗВ) предпочтительны, поскольку они связаны с меньшей частотой побочных эффектов [96]. Лекарственная форма трамадола в капсулах с микропеллетами на несколько единиц с ЗВ (Меда) обеспечивает длительное поддержание эффективного уровня трамадола в плазме с низкой вариабельностью скорости и степени абсорбции [97], таким образом предотвращая высокие пики концентрации в плазме, связанные с НР, которые отмечаются для лекарственных форм с немедленным высвобождением [96,97]. Кроме того, для повышения переносимости и минимизации случаев прекращения терапии по причине НР рекомендуется медленное повышение дозы трамадола с ЗВ от 50 до 100 мг 2 раза в день в течение 7 дней [98].…”
Section: трамадолunclassified
“…The multi-unit drug delivery system (MUDDS) had unique advantages over the single pellet system in the treatment of some diseases (Cnota 2005). Studies had shown that the double-release pellets MUDDS made by the mixture of immediate-release and sustained-release pellets according to a certain proportion not only could a 1547357926@qq.com b 930520491@qq.com c 1592974052@qq.com ensure the initial effect of the drug in vivo, but also make the stable release of MUDDS in vivo so that the efficacy and safety of the drug were significantly improved (Dong 2018, Shan 2022).…”
Section: Introdutionmentioning
confidence: 99%